2014
DOI: 10.1002/2014jd021589
|View full text |Cite
|
Sign up to set email alerts
|

Organic aerosol emission ratios from the laboratory combustion of biomass fuels

Abstract: Organic aerosol (OA) emission ratios (ER) have been characterized for 67 burns during the second Fire Laboratory at Missoula Experiment. These fires involved 19 different species representing 6 major fuels, each of which forms an important contribution to the U.S. biomass burning inventory. Average normalized ΔOA/ΔCO ratios show a high degree of variability, both between and within different fuel types and species, typically exceeding differen-ces between separate plumes in ambient measurements. This variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 51 publications
(78 reference statements)
5
41
1
Order By: Relevance
“…This comparison supports a downwind formation mechanism. Similar observations of minimal change in the 240 ΔOA/ΔCO have been previously reported (Jolly et al, 2012;Jolleys et al, 2014;Zhou et al, 2017).…”
supporting
confidence: 88%
“…This comparison supports a downwind formation mechanism. Similar observations of minimal change in the 240 ΔOA/ΔCO have been previously reported (Jolly et al, 2012;Jolleys et al, 2014;Zhou et al, 2017).…”
supporting
confidence: 88%
“…Weimer et al (2008) suggested that a low m/z 44 signal is indicative of the flaming phase whereas high signals occur during the smouldering phase. Contrastingly, Jolleys et al (2014b) found in- creased f 44 occurred more frequently during flaming combustion than smouldering burns. These opposing conclusions highlight the dependency of emissions from fires on a variety of factors, including burn conditions and fuel type.…”
Section: Role Of Burn Conditionsmentioning
confidence: 64%
“…Furthermore, BBOA evolves in the atmosphere through oxidation, whereby aged biomass burning aerosols have mass spectra similar to that of fulvic acid, used to represent highly oxidised OA with a large signal at m/z 44 (Capes et al, 2008;Grieshop et al, 2009;DeCarlo et al, 2010;Cubison et al, 2011;Lack et al, 2013). Consequently, it can sometimes be difficult to determine from the mass spectra and time series derived from PMF alone whether a factor represents primary SFOA, processed pri- mary SFOA, SOA formed from SFOA, or a mixture of SFOA and OOA which are co-emitted (e.g.…”
Section: Investigating the Behaviour Of Sfoamentioning
confidence: 99%
See 1 more Smart Citation
“…While the influence of the fuel (hardwood for stove A and B, softwood for stove C) cannot be neglected, we highlight, from our set of experiments, the overriding importance of the MCE on both the EF of organic markers and their relative contribution to OA. Previous studies have already revealed a relationship between the MCE and characteristics of the mass spectral signature of the OA emissions (Jolleys et al, 2014;Bertrand et al, 2017) but the influence of the MCE on individual organic marker emissions is still virtually unknown. The MCE values for the log woodstoves (stove A and B) range between 0.80 and 0.91 (Table 1), indicating that the combustion in these stoves is typically smoldering (MCE < 0.9), but also highly variable.…”
Section: Effect Of Burning Conditions On the Poa Chemical Compositionmentioning
confidence: 99%